Physical Properties and Antifungal Activity of Red Galangal (Alpinia purpurata K. Schum) Rhizome Extract in Oil-in-Water-Based Cream Against Trichophyton rubrum - Mulyaningsih, Sri; Ranila, Suciati; Fatimah, Siti Fatmawati (Clinical and Pharmaceutical Sciences Journal, 2025)
Trichophyton rubrum is a common fungus that causes a dermatophyte infection known as tinea cruris. More than a fifth of the population in Indonesia suffers from this infection.  Alpinia purpurata K. Schum or well known as red galangal is said to have antifungal properties because of its composition, which includes compounds such as volatile oil, acetyl chavicol, flavonoids, and phenols. This study was aimed to determine the antifungal activity of a oil-in-water-based cream containing red galangal rhizome extract (RGRE) against T. rubrum. RGRE was obtained by macerating the rhizomes in a solvent of 96% ethanol and evaporating until a thick extract was obtained. The extract was then formulated into an oil/water-based cream at concentrations of 10%, 15%, and 20%. The creams were evaluated for their physical properties, including organoleptic properties, homogeneity, pH, viscosity, adhesivity, and spreadability. The antifungal activity was tested using the agar diffusion method against T. rubrum. Data on the physical properties of the creams and their antifungal activity were analyzed using a one-way ANOVA test with a 95% confidence level. The results showed that creams with higher RGRE concentrations exhibited decreased spreadability and pH values but increased the viscosity and adhesivity test. The antifungal activity increased with higher RGE concentrations, starting at 10%, 15%, and 20%, with inhibition diameters of 12.33 mm, 18.83 mm, and 21.66 mm, respectively. Statistical analysis showed that RGE concentration affected the physical properties of the cream, including pH, spreadability, viscosity, adhesivity test as well as antifungal activity (p < 0.05). In conclusion, the water-in-oil-based cream containing 20% RGRE exhibits favorable physical properties and antifungal activity. Keywords: Cream, dermatophyte, diffusion method, viscosity, Zingiberaceae